1993
DOI: 10.1210/endo.133.6.8243274
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to physical and psychological stressors elevates plasma interleukin 6: relationship to the activation of hypothalamic-pituitary-adrenal axis.

Abstract: Interleukin 6 (IL-6) is a pleiotropic cytokine produced by the cells of immune and nonimmune origin. Increased production of IL-6 is associated with disturbances of homeostasis, such as trauma, sepsis, or inflammatory diseases. Endotoxemia, tissue injury, or immune inflammatory reactions as well as physical or psychological stress are known to cause increased production of IL-6. We have confirmed this by showing that rats exposed to electric footshock, physical restraint, or a conditioned aversive stimulus hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
182
1
7

Year Published

2000
2000
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 358 publications
(198 citation statements)
references
References 7 publications
7
182
1
7
Order By: Relevance
“…Many studies revealed that various psychological stressors alone can induce proinflammatory (IL‐1, IL‐6, TNF‐α) 15, 16, yet the mechanism and target cell for such cytokine production are not known for certain.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies revealed that various psychological stressors alone can induce proinflammatory (IL‐1, IL‐6, TNF‐α) 15, 16, yet the mechanism and target cell for such cytokine production are not known for certain.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that psychosocial stress induces neuroendocrine stress responses by stimulation of the hypothalamic-pituitaryadrenal (HPA) axis and thus increases circulating levels of IL-6, which in turn is an important regulator of CRP. 29,44,45 It is hypothesized that the relation between stress and CVD may partly be mediated by an increased susceptibility to infectious disease, although the predictive value of infectious biomarkers regarding coronary heart disease is uncertain. 46 For a long time, it has been suggested that psychologic distress may be associated with the onset of infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…This reduced GR response was related to high serum TNF-a and IL-6 levels. Since psychological or physical stress was shown to result in an enhanced IL-6 secretion in the peripheral immune system, [149][150][151] the functional relationship between cytokines and HPA axis activity is of pivotal interest in MD research. Psychological stress not only directly induce the activity of the HPA axis, but may also induce it indirectly through increased IL-6 levels.…”
Section: The Inflammatory Hypothesis Of Depressionmentioning
confidence: 99%